Validation of the Pelvic Organ Prolapse Simple Screening Inventory (POPSSI) in a population of Ethiopian women - Dawit Worku Kassa; Yirgu Gebrehiwot Ferede; Polina Advolodkina (BMC, 2019)
Abstract Background The incidence of Pelvic Organ Prolapse (POP) in the developing world is not known. A nonclinical screening tool for prolapse is needed in the resource poor setting. In this study, we aim to determine the validity of the Pelvic Organ Prolapse Simple Screening Inventory (POPSSI) for detection of POP in a population of women at two academic hospitals in Addis Ababa, Ethiopia. Methods Women from two teaching hospitals in Addis Ababa, Ethiopia were recruited to complete the POPSSI questionnaire as well as a Pelvic Organ Prolapse Quantification (POP-Q) exam. Descriptive data on exam findings were collected. Questionnaire responses were then correlated to exam findings and data analyzed to determine the validity of this test as a screening tool for prolapse in our patient population. Results Majority of the women with POP had advanced stage. The sensitivity and specificity of the POPSSI for identifying pelvic organ prolapse in our study patient population was 91.7 and 60.6% respectively. Conclusion The POPSSI has a high sensitivity for detecting women with POP. "Feeling or seeing bulge" had a higher sensitivity and specificity.